The Effect of Crossbreeding on Some Economic Traits for Chicks of Lohmann Chicken - Allawi Luaibi Dagher Al-Khauzai (Al-Qadisiyah Journal For Agriculture Sciences, 2020)
The experiment has been conducted at the poultry farm of Al-Qadisyah University, College of Agriculture, Department of Animal Production , for  the period 24/11/2018 till 10/4/2019 by using  80 hatching chicks which belong to 20 dams and 5 sires, each sire includes 16 chicks. Four chickens are put  with each sire, the first sire( Leghorn) crossbreeding with dams of Lohmann , the remaining sires are local cocks ,with five Lohmann hens. The chicks of each sire divided into two replicates ,each  replicate contains 8 chicks , the experiment continues for 42 days of age. The experiment aims to study the effect of sire groups on growth traits (weight at hatching , weight at 42 days of age , weight gain and daily weight gain ) Also , the effect of sire on weekly consumption feed , in addition to estimate the heritability for previous traits and the genetic correlations among these traits. The results can be summarized as follows :